Effective connectivity of the human mirror neuron system during social cognition - Sadeghi, Sadjad; Schmidt, Stephanie N. L.; Mier, Daniela; Haß, Joachim (Social cognitive and affective neuroscience, 2022)
The human mirror neuron system (MNS) can be considered the neural basis of social cognition. Identifying the global network structure of this system can provide significant progress in the field. In this study, we use dynamic causal modeling (DCM) to determine the effective connectivity between central regions of the MNS for the first time during different social cognition tasks. Sixty-seven healthy participants completed fMRI scanning while performing social cognition tasks, including imitation, empathy and theory of mind. Superior temporal sulcus (STS), inferior parietal lobule (IPL) and Brodmann area 44 (BA44) formed the regions of interest for DCM. Varying connectivity patterns, 540 models were built and fitted for each participant. By applying group-level analysis, Bayesian model selection and Bayesian model averaging, the optimal family and model for all experimental tasks were found. For all social-cognitive processes, effective connectivity from STS to IPL and from STS to BA44 was found. For imitation, additional mutual connections occurred between STS and BA44, as well as BA44 and IPL. The results suggest inverse models in which the motor regions BA44 and IPL receive sensory information from the STS. In contrast, for imitation, a sensory loop with an exchange of motor-to-sensory and sensory-to-motor information seems to exist.
Online veröffentlicht: 27. Januar 2022
Gesehen am 27.08.2024